2017
DOI: 10.1002/jcb.25817
|View full text |Cite
|
Sign up to set email alerts
|

PPARα Promotes Cancer Cell Glut1 Transcription Repression

Abstract: Abundant nutrient availability including glucose and amino acids plays an important role in maintaining cancer cell energetic and biosynthetic pathways. As a nuclear receptor, peroxisome-proliferator-activated receptor α (PPARα) regulates inflammation and cancer progression, however, it is still unclear the interaction of PPARα with the cancer cell glucose metabolism. Here we found that PPARα reduced Glut1 (Glucose transporter 1) protein and gene levels in HCT-116, SW480, HeLa, and MCF-7 cancer cell lines. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
(36 reference statements)
1
25
0
Order By: Relevance
“…The immunofluorescence results indicated that chronic stress induced global changes of hippocampal PPARα distribution. As a nuclear receptor, PPARα has the main physiological function of modulating the transcriptional activities of some genes, including those for Glut1, CREB, Mogat1 and HO‐1, by binding PPREs (Roy et al ., ; Sankella et al ., ; Wu et al ., ; You et al ., ). Among these genes, CREB is well known to participate in depression (Blendy, ; Gass and Riva, ; Krishnan and Nestler, ).…”
Section: Discussionmentioning
confidence: 97%
“…The immunofluorescence results indicated that chronic stress induced global changes of hippocampal PPARα distribution. As a nuclear receptor, PPARα has the main physiological function of modulating the transcriptional activities of some genes, including those for Glut1, CREB, Mogat1 and HO‐1, by binding PPREs (Roy et al ., ; Sankella et al ., ; Wu et al ., ; You et al ., ). Among these genes, CREB is well known to participate in depression (Blendy, ; Gass and Riva, ; Krishnan and Nestler, ).…”
Section: Discussionmentioning
confidence: 97%
“…Even though the PPARs family contains PPARα, PPARγ and PPARδ, they serve as different functions in tumor development. Increasing evidences show that PPARα [ 2 , 10 12 ] or PPARγ [ 7 , 8 , 13 ] inhibits tumor progression, which acts as tumor suppressors, while some reports show that PPARα is associated with tumor progression [ 14 16 ]. In contrast, PPARδ promotes tumor development [ 3 , 6 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glut1 plays a critical role in glucose uptake to regulate cancer cell metabolism, which is widely expressed in most types of cancer cells [ 24 , 25 ]. PPARα can directly inhibit Glut1 transcription by binding Glut1 potential PPRE motif [ 2 ]. The synthetic ligands of PPARα including fenofibrate, clofibrate and wyeth14,643 suppress cell proliferation by inducing apoptosis and cell cycle arrest involved in inhibition of NFκB [ 26 ] and activation of caspase-3 [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, fenofibrate could increased FAO resulting in high acyl group levels useful for TCA reaction [126,129]. Regarding to Warburg effect and related glycolysis, it was reported the repression activity of PPARα on GLUT1 gene with reduced glucose uptake, these evidences were obtained in different cancer cell line (HCT-116, SW480, MCF-7 and HeLa) [70].…”
Section: Pparα and Cancer Metabolismmentioning
confidence: 98%
“…To date research activity has yielded conflicting evidence in this regard. There are different results about the tumour suppression related to PPARα and PPARγ transcriptional activation [64][65][66][67][68][69][70], but likewise proofs of their cancer promotion activity [71][72][73]; instead regarding PPARβ/δ activity the majority of study conducted shows its oncogenic role [74][75][76]. Although it must be emphasized that PPARs behaviour, both as pro-or anti-tumour, is strictly dependent on the tissue type and tumour microenvironment.…”
Section: Pparsmentioning
confidence: 99%